THE EFFECTIVENESS OF INFOGRAPHIC IN TEACHING READING COMPREHENSION - RINA FALENTINA; Desi Sri Astuti; Dian Shinta Sari (XXXX-XXXX, 2022)
This research was conducted to investigate the effectiveness of infographic in teaching reading comprehension and how significance the effectiveness of infographic are in students reading comprehension at SMA N 01 Lumar. The form of this study was a Pre-Experimental Study with a one-group pre-test and post-test design. The Population of the research was students at Tenth Grade Students of SMA N 01 Lumar in the Academic Year of 2020/2021. The sample of this research was X IPA I selected using a cluster random sampling technique. The technique of data collection applied in this research is measurement. The tool of this research was a test. The researcher ask the validator and conduct the tryout to the test before the test was given to the sample to get the validity of the test. The multiple-choice that consists of 20 items in this research were used to get the data after implementation of the infographic. The data was analyzed by used SPSS 26. The results of this research showed that the infographic was effective in teaching reading comprehension and there is a modest significant difference effect. Suggested to the future researcher presents the great and interesting in infographic presentation